(untitled) - Toynbee, Arnold J. (London, 1934)
The range of challenge and reponse: The stimulus of hard countries, the stimulus of new ground, the stimulus of blows, the stimulus of pressures....
Keywords: Civilization,History,Lịch sử,Nền văn minh; Philosophy,Triết học